KARAKTERISTIK TEPUNG KACANG MERAH HASIL AUTOCLAVING, COOLING, DAN AUTOCLAVING-COOLING [CHARACTERISTICS OF AUTOCLAVED, COOLED AND AUTOCLAVED-COOLED RED KIDNEY BEAN FLOUR] - Anugrahati, Nuri Arum; Widjanarko, Angela Maria (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2018)
The characteristics of autoclaved, cooled and autoclaved-cooled red kidney bean flour were studied. Autoclaving was done at 121°C for 15 min while cooling was done at 6°C for 24h. The parameters of red kidney been flour were resistant starch, starch, amylose content, proximate and X-ray diffraction pattern. Resistant starch content (6.23%) and amylose (8.38%) of autoclaved-cooled red kidney flour is higher than control and cooled red kidney bean flour. Autoclaved-cooled red kidney flour has 6.20% of water, 3.97% of ash, 20.79% of protein, 2.84% of fat, and 66.21% of carbohydrate. The X-ray diffraction pattern of autoclaved-cooled red kidney flour is B type with diffraction peaks at 17, 19 and 22 ° 2Î¸.ABSTRAK Karakteristik tepung kacang merah hasil autoclaving, cooling, dan autoclaving-cooling telah diteliti. Autoclaving dilakukan pada suhu 121°C selama 15 menit sedangkan cooling dilakukan pada suhu 6°C selama 24 jam. Parameter tepung kacang merah yang diuji meliputi kadar pati resisten, pati, amilosa, proksimat, dan pola difraksi X-ray. Autoclaving-cooling menghasilkan kadar pati resisten (6,23%) dan amilosa (8,38%) tepung kacang merah yang lebih tinggi dibandingkan tepung kacang merah kontrol dan hasil cooling. Tepung kacang merah hasil autoclaving-cooling memiliki kadar air 6,20%, abu 3,97%, protein 20,79%, lemak 2,84%, dan karbohidrat 66,21%. Pola difraksi sinar X tepung kacang merah hasil autoclaving-cooling adalah tipe B dengan puncak difraksi pada 17, 19, dan 22° 2Î¸. Kata kunci : Autoclaving-cooling, tepung kacang merah